Real-time high-speed mobility management - Ahmed Abdelsalam Abuelgasim; Mohamed Khalafalla Hassan; Mutaz Hamed Khairi; Muhammad Nadzir Marsono; Kamaludin Mohamad Yusof (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
High-speed mobility system has now become a serious concern for mobile operators due to the large frameworks of a heterogeneous network made up of multiple cell types and different frequency bands. Handover (HO) is conducted in a real-life scenario when the user equipment (UE) moves from one network coverage to another by performing proper measurement with high speed. HO breakdown and call loss are observed due to a high speed; thus, high-speed mobility system needs improvement by using the UE speed as one of the key measurement monitoring criteria for the long-term evolution (LTE) network. Vendor consultation has been considered in this paper in addition to real drive test measurement in highways. Results have shown that velocity has a direct impact on the handover quality and overall timing. Results also demonstrate that 120 km/h measurement is better than 140 km/h as UE speed.